Oxidation of cadaverine by putrescine oxidase from Rhodococcus erythropolis. Issue 10 (29th July 2021) - Anyanwu, Valentine E; Hall, Stephen J; Stephens, Gill; Pordea, Anca
Abstract: BACKGROUND: Putrescine oxidase (EC 1.4.3.10) is of interest for the microbial production of unsubstituted platform nitrogen ( N ‐)heterocycles, because it only requires inexpensive oxygen as co‐substrate. Putrescine oxidase from Rhodococcus erythropolis (Re‐PuO) was shown previously to catalyze the oxidation of cadaverine; however, there is little information in the literature about the robustness of this enzyme for biotechnological applications. The aim of this study was to investigate the suitability of Re‐PuO for the bioproduction of 1‐piperideine from cadaverine under different reaction conditions. RESULTS: The formation of 1‐piperideine catalyzed by Re‐PuO was demonstrated using o ‐aminobenzaldehyde as a reagent to trap the cyclic imine and shift the equilibrium for cyclization. A direct assay of Re‐PuO activity for cadaverine oxidation was then implemented, by monitoring oxygen consumption. Characterization of the reaction mixture by 1 H NMR and mass spectrometry confirmed the presence of piperideine dimers and trimers, yet the quantification of the reaction products could not be achieved. The optimum temperature and pH conditions for enzyme activity were determined as 55 °C and 8.5, respectively. At pH 7.5, the enzyme retained its activity after 65 h incubation at 25 °C, but lost 75% of its activity after 1 h incubation at 55 °C. The enzyme showed no substrate inhibition at concentrations as high as 100 mmol L –1 cadaverine. Complete biotransformation of cadaverine was observed in whole cells at physiological conditions. CONCLUSIONS: These results successfully demonstrate the potential of putrescine oxidase for the bioproduction of N ‐heterocycles from cadaverine. © 2021 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).